The Impact of Medical Device Associated Candida Infections on Immunocomprised Patient Outcomes in A Tertiary Care Settings - Dung, Nikita Dung; D. Neha; Anju Thomas; Jeas John (Jurnal Vokasi Kesehatan, 2024)
Medical practice across all specialties increasingly relies on the insertion or implantation of medical devices, yet these interventions carry inherent risks of bacterial and fungal infections of particular concern is the shifting epidemiology of Candida infections, where non-albicans Candida species now predominate in cases of hematogenously disseminated candidiasis in many healthcare institutions. These device-associated Candida infections represent a significant threat to patient outcomes, characterized by the organism's ability to adhere to device surfaces and proliferate as multicellular communities within self-produced extracellular matrices. The pathogenic process involves colonization of foreign materials, including intravascular catheters, urinary catheters, dentures, and various implanted medical devices, leading to resistant infections that are particularly challenging to treat. These device-associated infections can progress to Candida bloodstream infections, which are associated with significant mortality rates. However, research indicates that optimized diagnostic approaches and therapeutic management strategies can substantially improve patient outcomes. This mini-review aims to identify and address frequently overlooked opportunities in the management of device-associated Candida bloodstream infections, with particular emphasis on Early recognition and diagnosis of device-associated infections. Implementation of evidence-based preventive measures. Optimization of therapeutic interventions. Special considerations for high-risk and immunocompromised patients.